Estudio de prefactibilidad para la producción y comercialización de limón tahití en el cantón Santa Rosa - Cabrera López, Jorge Luis (2012)
The project is planned at the corner of Santa Rosa in the province of El Oro, and had the following objectives: To investigate and understand the technology of crop production, prepare a market study that allows us to know the offer and determine unmet demand in the market and an economic study and financial order to determine the financial viability of the project. To which the variable planted hereinafter laid; costs of production, marketing, project profitability, product pricing, and production volume. Using bibliographic methodology system, economic and financial. The financial evaluation presents an adjusted net present value of $ 10%. 3 309.19 and an Internal Rate of Return of 10%, and Ecuador has special permission for export of Tahiti lime as the APHIS states that this product is free from the attack of the fruit fly, the United States of North America is our main customer, taking as the best opportunity for this type of product is that the harvest is between the months of February to April, which means a window shopping in our favor, noting that to implement this project requires funding long term, it has the largest producers in Central America that cater to markets in the U.S. and Europe, noting that the breakeven point for this project is in the production of 75 units for 18 825,86 (sale price ) equivalent to $. 1 364 865,48